Analisis Laju Pertumbuhan Dan Efektifitas Penerimaan Retrisubi Pengujian Kendaraan Bermotor Pada Dinas Perhubungan Kabupaten Malang - Angguliyah Rizqi Amaliyah (INVENTORY: JURNAL AKUNTANSI, 2020)
Implementation of this research aims to analyze the rate of growth and effectiveness of the acceptance of the test retribution of motor vehicles (PKB) at the District Transportation Service Malang in 2015 to 2019. In this study techniques in collecting data IE primary data and secondary data. Based on the results of documentation, interviews and observations on the Transportation Service Department of Motor vehicle testing. Based on the results of research that has been done shows the level of growth of motor vehicle testing in Malang district from 2015 to 2019 with an average of 6.83% (positive category). Percentage rate of growth in the matrix of potential retribution of motorised vehicle test is included in the prime category so that it becomes the mainstay sector for Malang Regency government. As well as belonging to the developing category because of its potential contribution to increased growth rate (positive). Calculation results at the level of effectiveness during the year 2015 to 2019 shows an average of 102.19%. Percentage level of effectiveness demonstrated the performance of the district government of Malang in the Department of Transportation in receipt of the test retribution of motor vehicles, including the category is very effective on every duty and capable of management and managing the acceptance of the test retribution of motor vehicles.Keywords; Growth Rate; Effectiveness; Motorized Vehicle Testing Levies